49 HYPOZINCEMIA AND OXIDATIVE STRESS IN RATS WITH CHRONIC ALDOSTERONISM. (1st January 2006) - Thomas, M.; Vidal, A.; Bhattacharya, S. K.; Ahokas, R. A.; Johnson, P. L.; Sun, Y.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: A chronic activation of the circulating renin-angiotensin-aldosterone system, which contributes to a salt-avid state and appearance of congestive heart failure (CHF), is accompanied by a systemic illness. Featured is the presence of reactive oxygen and nitrogen species in such diverse tissues as skin, skeletal muscle, heart, peripheral blood mononuclear cells (PBMC), and blood plasma. This altered redox state appears when endogenous antioxidant defenses are overwhelmed or when they are deficient. Zinc is a micronutrient integral to Cu/Zn superoxide dismutase (Cu/Zn SOD) activity; it protects against superoxide-mediated cytotoxicity. Urinary Zn excretion is increased in chronic hyperparathyroidism (HPT). We hypothesized that hypozincemia would accompany the secondary HPT seen with chronic aldosterone/salt treatment (ALDOST) and thereby would compromise Cu/Zn SOD activity. Methods: In plasma, we monitored Zn, parathyroid hormone (PTH), and a1 -antiproteinase (AP) activity, an inverse correlate of oxidative stress. In PBMC we measured total SOD activity and that of its isoforms, Cu/Zn-SOD and Mn-SOD. Uninephrectomized rats received ALDOST (0.75 μg/h and 1% NaCl/0.4% KCl in drinking water) and were compared to untreated age-/gender-matched controls. Results: In ALDOST vs controls, we found that Zn was reduced (95.2 6 3.5 vs 110 6 1.5 μg/dL, p < .05); PTH was increased (87 6 11 vs 53 6 10 pg/mL, p < .05); and a1-AP activity was reduced (22.9 6 1.4 vs 36.8 6 0.9 μmol/L, p < .001). Cu/Zn-SOD activity was reduced (p < .05) compared to controls (3.97 6 0.26 vs 4.99 6 0.09 U/mg total protein) and accounted for the decline in total SOD activity (4.58 6 0.29 vs 5.56 6 0.10 U/mg total protein, p < .05), whereas MnSOD activity, representing a smaller component of total SOD activity in PBMC, was unchanged (0.58 6 0.05 vs 0.60 6 0.04 U/mg total protein). Conclusions: Hypozincemia accompanies the secondary HPT found in rats with aldosteronism, where it may contribute to the systemic appearance of oxidative stress, including reduced plasma a1-AP activity and PBMC Cu/Zn SOD activity. Our findings suggest that monitoring of serum Zn and its supplementation could be beneficial in patients with CHF.